ANALISIS KUALITAS PEMBIAYAAN PERBANKAN SYARIAH TAHUN 2006-2010 - Dewi Indriana; Idah Zuhroh (Jurnal Ekonomi Pembangunan, 2012)
The research is quantitative descriptive research done in three banks titled: “Analysis of Financing Quality in Syariah Banks Period 2006-2010”. The research purpose is to find out how much given debt influence  and Loan to Assets Ratio (LAR) to Non Performing Loan. In this research, researcher took hypothesis that there’s a significant influence between given debt, Loan to Assets Ratio (LAR) to Non Performing Loan in Syariah Banks period 2006-2010. From the result, it is found determination coefficient (R2) for data regression 0,467. It means that independence variable altogether are able to explain 47% variance of dependent variables, which is Non Performing Loan. Then from t test, it is found that given-debt variable has significant influence to NPL, it is proven that Tcount > Ttable, while LAR has unsignificant influence, it’s proven that Tcount < Ttable and after f test, it is found that given-debt variable and LAR overall has significant influence to NPL.  From data analysis done at once, it’s shown that debt variable given has more significant result to NPL than LAR, which is 0,677%.